Aspek Perilaku Dalam Overconfidence: Analysis Bibliometric - Devi, Wiara Sanchia Grafita Ryana; Pranata, Rengga Madya (LPPM Universitas Buana Perjuangan Karawang, 2024)
ABSTRACT Abstract This research aims to conduct a bibliometric analysis of bias overconfidence published from 2017 to 2023. The Crossref database is used to gather information on studies related to overconfidence. A total of 2105 articles have been collected with the keyword